Use of flaps in orthopedics in a peripheral trauma center in Nepal without plastic surgery services - Bhim Bahadur Shreemal; Tul Bahadur Pun; Dipak Maharjan; Devendra Singh Bhat (Wolters Kluwer Medknow Publications, 2021)
Background: Soft tissue cover after surgical debridement, skeletal stabilization is an integral part of optimal management of high-velocity orthopedic injuries and orthopedic infections which is preferably done in collaboration with plastic surgeons. In our peripheral hospital, since plastic surgery service is not available, it has been our practice as orthopedic surgeons to be involved in the comprehensive surgical care of such patients including flap cover of the resulting soft-tissue defect. We reviewed the results of our flaps from June 2013 to May 2015 which were exclusively done by orthopedic surgeons. Materials and Methods: All patients from June 2013 to May 2015 with an open fracture or orthopedic infections who underwent flap cover of any kind in both the upper and lower limbs were retrospectively reviewed. Results: We had thirty-eight flaps in 36 patients. Two were lost to follow-up. There were eight (22.22%) upper limb flaps and 28 (77.77%) lower limb flaps. Average follow-up was 3 months (6 weeks-12 months). The average age was 35 years (17 years-65 years). Ten (27.7%) of the patients had flap done for infection and the rest 26 (72.2%) for an open fracture. The dimension of the flap ranged from 1 cm × 1 cm to 15 cm × 16 cm. Thirty-one out of thirty-six (83.33%) of the flaps healed primarily. Six (16.66%) patients had minor complications. There was no total flap loss. Conclusion: Comprehensive care of soft-tissue defects by orthopedic surgeons themselves seem to be a viable option with good outcome and acceptable complications in orthopedic trauma and infections when plastic surgery service in not available.